Perceived value análisis and disinformation applied to e-cigarettes - Villanueva Blasco, Víctor; Akardas, Merve; Isorna-Folgar, Manuel; Rey-Pino, Juan Miguel (Acciones e Investigaciones Sociales, 2023)
Tobacco, and its main component, nicotine, continues to be one of the main health problems worldwide. The use of electronic cigarettes (EC) is currently increasing. The objective was to analyze the perceived value and motivations for the consumption of nicotine through e-cigarettes and their convergence with the disinformation and marketing strategies of the tobacco industry. Methods. A qualitative methodology was used through a review focused on the perceived value of nicotine and its usual consumption technologies, and in-depth interviews with 15 university students. Results. Several components of the perceived value of the nicotine-consuming experience through EC versus conventional cigarettes are identified, in line with the industry’s disinformation and fake news dissemination strategy. These refer to EC as less harmful, clean, attractive and facilitating products for the cessation of tobacco use. Conclusions. It is evident how brands are taking advantage of the limited rationality of the consumer in their decision making through the marketing communication made, based on disinformation and fake news. Further research is needed into industry strategies to promote nicotine use in the population, especially among young people.